Embedded evolvable fuzzy hardware systems for cell flow scheduling - Li, Ju Hui (2008)
Evolvable hardware (EHW) has become a promising branch of research in the area of hardware architecture. However, there remain many issues to be tackled before EHW can be applied more extensively in real-time problems. The three major open issues are on-line adaptation, scalability and evolution termination. In this thesis, we propose the concept of an intrinsic evolvable and on-line adaptive evolvable fuzzy hardware (EFH). Adopting our proposed EFH, the three major open problems can be addressed. In particular, EFH has great potential for solving real-time control problems efficiently. In order to demonstrate our idea, we apply the EFH to tackle the problem of ATM cell-scheduling.